Implementation of capacitance as simultaneous sensing and actuating tool in tapered microelectrode arrays for dielectrophoresis-on-a-chip application - Buyong, M.R. (Emerald Group Holdings Ltd., 2020)
Purpose: This paper aims to present the capacitance characterization of tapered dielectrophoresis (DEP) microelectrodes as micro-electro-mechanical system sensor and actuator device. The application of DEP-on-a-chip (DOC) can be used to evaluate and correlate the capacitive sensing measurement at an actual position and end station of liquid suspended targeted particles by DEP force actuator manipulation. Design/methodology/approach: The capability of both, sensing and manipulation was analysed based on capacitance changes corresponding to the particle positioning and stationing of the targeted particles at regions of interest. The mechanisms of DEP sensor and actuator, designed in DOC applications were energized by electric field of tapered DEP microelectrodes. The actual DEP forces behaviour has been also studied via quantitative analysis of capacitance measurement value and its correlation with qualitative analysis of positioning and stationing of targeted particles. Findings: The significance of the present work is the ability of using tapered DEP microelectrodes in a closed mode system to simultaneously sense and vary the magnitude of manipulation. Originality/value: The integration of DOC platform for contactless electrical-driven with selective detection and rapid manipulation can provide better efficiency in in situ selective biosensors or bio-detection and rapid bio-manipulation for DOC diagnostic and prognostic devices. Â© 2020, Emerald Publishing Limited.